Azithromycin Prescribing by Respiratory Pediatricians in Australia and New Zealand for Chronic Wet Cough: A Questionnaire-Based Survey - Chellew, Naomi; Chang, Anne B.; Grimwood, Keith (Frontiers in Pediatrics, 2020)
Aims: To determine how respiratory paediatricians across Australia and New Zealand prescribe azithromycin for children with chronic wet cough, including recurrent protracted bacterial bronchitis, chronic suppurative lung disease (CSLD) and bronchiectasis. Methods: A prospective web-based questionnaire was emailed to members of the Paediatric Special Interest Group of the Thoracic Society of Australia and New Zealand (TSANZ) between April and May 2018. It comprised eight demographic and 15 clinically focused questions. Results: Of the 73 respiratory paediatricians listed across Australia and New Zealand, 29 (40%) responded and all prescribed azithromycin for chronic wet cough. Twelve (41%) indicated that they would consider prescribing a short-course (2-4 weeks) of azithromycin for children with a chronic wet cough. Although most respondents reported prescribing long-term (>4-weeks) azithromycin for either CSLD (n=23, 79%) or bronchiectasis (n=24, 83%), only nine (31%) respondents would commence treatment if in the previous 12-months these children experienced three non-hospitalised exacerbations and just 12 (41%) would do so if there had been two hospitalisations for severe exacerbations during the same period in accordance with the TSANZ national guidelines. A lower threshold for prescribing azithromycin was described for Indigenous children or if co-morbidities were present. None prescribed azithromycin for >24-months. Macrolide-resistance was reported in Streptococcus pneumoniae and Staphylococcus aureus. Conclusion: Although Australian and New Zealand respiratory paediatricians in this survey prescribed azithromycin for chronic wet cough most often in children with either CSLD or bronchiectasis, many did so outside the current national guidelines. Reasons for this need exploring.